2004
DOI: 10.1055/s-2004-828376
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation der deutschen Typ-D-Skala (DS14) und Prävalenz der Typ-D-Persönlichkeit bei kardiologischen und psychosomatischen Patienten sowie Gesunden

Abstract: The Type D personality pattern, consisting of negative affectivity and social inhibition, has been shown by Denollet et al. to predict adverse prognosis in patients with coronary heart disease. For measuring the Type D characteristics, Denollet has devised the 14 item Type D scale (DS14). In the present study, this instrument was translated into German. The validity, reliability and adequacy of the German DS14 were then tested in 2421 persons, including cardiological and psychosomatic patients as well as healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1
26

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 13 publications
4
37
1
26
Order By: Relevance
“…This was similarly reported by Grande et al (2004), who found the prevalence of Type D personality in psychosomatic patients being 62%. Possibly, those patients experience more distress that links both to mental health impairment and Type D.…”
Section: Discussionsupporting
confidence: 82%
“…This was similarly reported by Grande et al (2004), who found the prevalence of Type D personality in psychosomatic patients being 62%. Possibly, those patients experience more distress that links both to mental health impairment and Type D.…”
Section: Discussionsupporting
confidence: 82%
“…It has been argued that psychological research needs to explore newer personality constructs such as type-D to see how such constructs may contribute to our understanding of the pathogenic effects of personality on the development and progression of heart disease [49]. Accumulated evidence suggests that type-D personality is associated with increased risk of mortality, morbidity, and impaired quality of life in cardiac patients [50], and that the type-D construct is equally applicable across different nationalities (e.g., [51,52]). …”
Section: Discussionmentioning
confidence: 99%
“…Type D personality was assessed with the German version of the DS14 [1,5]. The DS14 comprises two reliable subscales with 7 items each for negative affectivity and social inhibition, rated on a 5-point Likert scale (0 = false to 4 = true).…”
Section: Methodsmentioning
confidence: 99%
“…Type D subjects were less educated and had a lower income in an age-adjusted analysis. Somewhat higher prevalence rates were found among clinical groups: in cardiovascular patients, these ranged from 24.8% in Germany (n = 1,196 [5]) to 28% in Belgium (n = 358 [1]). However, the highest rates, i.e.…”
Section: Introductionmentioning
confidence: 99%